2005
DOI: 10.1371/journal.pcbi.0010047.eor
|View full text |Cite
|
Sign up to set email alerts
|

Entropic stabilization of proteins and its proteomic consequences

Abstract: Evolutionary traces of thermophilic adaptation are manifest, on the whole-genome level, in compositional biases toward certain types of amino acids. However, it is sometimes difficult to discern their causes without a clear understanding of underlying physical mechanisms of thermal stabilization of proteins. For example, it is well-known that hyperthermophiles feature a greater proportion of charged residues, but, surprisingly, the excess of positively charged residues is almost entirely due to lysines but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 52 publications
3
20
1
Order By: Relevance
“…We interpret SdiffN as related to conformational flexibility, for sidechains, so that the current result is roughly in accord with the observation [48] that any increase in sidechain flexibility in thermophile proteins compared to mesophile proteins is small. It has been hypothesised that the basis for thermophile proteins containing a greater proportion of Lys over Arg, is a difference in the number of accessible rotameric states [48]. In a subsequent section we look at variations in dehydration energy that could contribute to changes in the percentages of charged residue classes.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…We interpret SdiffN as related to conformational flexibility, for sidechains, so that the current result is roughly in accord with the observation [48] that any increase in sidechain flexibility in thermophile proteins compared to mesophile proteins is small. It has been hypothesised that the basis for thermophile proteins containing a greater proportion of Lys over Arg, is a difference in the number of accessible rotameric states [48]. In a subsequent section we look at variations in dehydration energy that could contribute to changes in the percentages of charged residue classes.…”
Section: Resultssupporting
confidence: 88%
“…The greatest difference in amino acid composition between mesophile and hyperthermophile proteins was their proportion of titratable residues (Figure 4a), being higher for hyperthermophiles [16,18,22], with the largest changes for Glu and Lys [48,69]. We see a small decrease in the proportion of Asn [8], in common with other polar residues that do not carry net charge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and Table 1), which is in agreement with a low relative arginine content [Arg/(Arg + Lys)], a typical characteristic of several cold-adapted enzymes [2,4,5,7]. It has been suggested that lysine residues stabilize the folded state through increased rotameric states and thereby reducing the entropic penalty of going from the unfolded to the folded state when compared to arginine [38]. SE has 7 Lys and 6 Arg residues while the corresponding numbers are 3 and 12 for PE, and from an entropic point of view this will increase the stability of the SE relative to PE.…”
Section: D Localization and Solvent Accessibility Degree Of The Charsupporting
confidence: 76%
“…Similar to the situation in cold adaptation, the intrinsic properties of nucleic acids, lipids and enzymes/proteins allow thermophiles to flourish in high temperature environments, and specific composition biases and structural adaptations have been identified [16,[28][29][30][31]. Recent publications describing the genomes of two hyperthermophilic archaea (Nanoarchaeum equitans and Thermococcus kodakaraensis [32 ,33]), one archaeal thermoacidophile (Sulfolobus acidocaldarius) [34] and one thermophilic bacterium (Carboxydothermus hydrogenoformans) [35], although not significantly changing the perception of high temperature adaptation, bring together several exciting novelties on various aspects of the biology, genome evolution and metabolic versatility in specific thermophilic environments.…”
Section: Extremophile Genomics Expose Biotechnological Potentialmentioning
confidence: 97%